IMPORTANCE & DEMAND OF EGG PRODUCTION IN TO SOCIETY - P, Pro. Ramanjudar P; Keduna, Pro. Kadiappa (International Journal of Multidisciplinary Research and Studies, 2021)
The attributes of egg production that elicit values-based responses include the worth and availability of eggs, environmental impacts, food safety or health concerns, and animal welfare. Different social groups have distinct interests regarding the sustainability of egg production that reflect these diverse values. Current scientifically based knowledge about how values and attitudes in these groups are characterized is uneven and must be derived from studies conducted at varying times and using incomplete study methods. In general, some producer and consumer interests are translated through markets and are mediated by market mechanisms, whereas others are poorly reflected by economic behavior. An array of survey and focus group research has been performed to elicit consumer and activist beliefs about performance goals they’d expect from an egg production system. These studies provide evidence that consumers’ market behavior could also be at odds with their ethics and philosophy about performance goals.